2018
DOI: 10.1002/aocs.12103
|View full text |Cite
|
Sign up to set email alerts
|

Application of Barley‐ and Lentil‐Protein Concentrates in the Production of Protein‐Enriched Doughnuts

Abstract: Barley and lentil proteins have good emulsifying and foaming capacity, which make them suitable ingredients in many food formulations. The aim of this research was to develop protein-enhanced foods based on barley and lentil proteins using doughnut as a food model. In enriched doughnut formulations, barley proteins were used to substitute for 20% of the wheat flour (doughnuts labeled as barley doughnut, barley/lentil doughnut [BLD], and vegan doughnut [VD]) and lentil proteins were used as an egg replacer (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Supplementation of WF in preparation of donuts was also reported by several authors as like with barley-and lentil-protein concentrates (Eckert et al, 2018), Persian gum and carrot pomace powder (Mehran et al, 2017), bread fruit flour (Oke et al, 2018), banana (Musa paradisiaca L. var. Awak) flour (Chong & Noor Aziah, 2008), etc.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Supplementation of WF in preparation of donuts was also reported by several authors as like with barley-and lentil-protein concentrates (Eckert et al, 2018), Persian gum and carrot pomace powder (Mehran et al, 2017), bread fruit flour (Oke et al, 2018), banana (Musa paradisiaca L. var. Awak) flour (Chong & Noor Aziah, 2008), etc.…”
mentioning
confidence: 58%
“…Dhingra and Jood (2001);Sharma and Chauhan (2000) as they found and reported that high-protein content flour supplementation increased the protein content of final products Eckert et al (2018). reported 3.9 ± 0.1% protein in their control donuts but high-protein-containing flour substitution increased the protein content up to 9.5 ± 0.2%.…”
mentioning
confidence: 93%
“…Lentil protein concentrates have been used to replace eggs in production of protein-enriched doughnuts [155], angel food cake, and muffins [156]. Lentil flour was used to make gluten-free crackers [157], lentil flour with transglutaminase has been used as a binding agent to make protein-enriched restructured beef steaks or beef patties [158,159], and lentil protein isolates have been used as an emulsifier to produce salad dressings [160].…”
Section: Food Applications Of Lentil Proteinsmentioning
confidence: 99%
“…10 Its application can be categorized into two main sectors: (1) food and beverages; and (2) other applications such as animal feed, cosmetic products, pharmaceuticals, biofuels, and nutraceuticals. 11 − 14 It has been used in the diets of many countries worldwide such as the Middle East, Russia, Poland, Tibet, Japan, North African countries, and India. It can be in meals such as soups, stews, casseroles, different kinds of pastas, noodles, and bakeries to produce flat bread and pastries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, barley glutelin proteins have demonstrated oil-binding capacities and considerable emulsifying stability, while barley hordein showed good foaming properties which provide opportunities for value-added food applications for barley protein. 14 18 The impact of these proteins on the final product will be discussed later in this paper. The use of barley as a high-quality protein ingredient in confectionary products has shown the potential to improve product flavor, texture, and storage stability.…”
Section: Introductionmentioning
confidence: 99%